RNA phloem transport mediated by pre-miRNA and viral tRNA-like structures. (July 2019) - Lezzhov, Alexander A.; Atabekova, Anastasia K.; Tolstyko, Eugeny A.; Lazareva, Ekaterina A.; Solovyev, Andrey G.
Highlights: tRNA-like structures of three plant viruses can enable the RNA phloem transport. A miRNA precursor can render RNA competent for the phloem transport. Sequences of miRNA precursors are found in pumpkin phloem transcriptome. Abstract: Phloem-mobile mRNAs are assumed to contain sequence elements directing RNA to the phloem translocation pathway. One of such elements is represented by tRNA sequences embedded in untranslated regions of many mRNAs, including those proved to be mobile. Genomic RNAs of a number of plant viruses possess a 3′-terminal tRNA-like structures (TLSs) only distantly related to genuine tRNAs, but nevertheless aminoacylated and capable of interaction with some tRNA-binding proteins. Here, we elaborated an experimental system for analysis of RNA phloem transport based on an engineered RNA of Potato virus X capable of replication, but not encapsidation and movement in plants. The TLSs of Brome mosaic virus, Tobacco mosaic virus and Turnip yellow mosaic virus were demonstrated to enable the phloem transport of foreign RNA. A miRNA precursor, pre-miR390b, was also found to render RNA competent for the phloem transport. In line with this, sequences of miRNA precursors were identified in a Cucurbita maxima phloem transcriptome, supporting the hypothesis that, at least in some cases, miRNA phloem signaling can involve miRNA precursors. Collectively, the data presented here suggest that RNA molecules can be directed into the phloem translocation pathway by structured RNA elements such as those of viral TLSs and miRNA precursors.